Pengaruh Pemberian Pupuk NPK Mutiara dan Ekstrak Kecambah Kacang Hijau Terhadap Pertumbuhan dan Hasil Tanaman Tomat (Lycopersicum Esculentum Mill.) Varietas Mawar - Qudsi Agil, Ahmad; Furoidah, Nanik (Program Studi Agroteknologi, 2025)
Tomatoes are one of the vegetables rich in vitamins and minerals, and are widely consumed as a spice, garnish, and a salad. Chemical fertilisation alone can pollute the environment and leave harmful residues; therefore, it is necessary to provide integrated inputs with natural ingredients during cultivation. The purpose of this study was to determine the effect of the interaction of the dose of NPK Mutiara fertiliser and mung bean sprout extract on the growth and yield of rose variety tomato plants. This study was conducted using a Randomised Block Design with a Factorial 3 x 3 in 3 replications. The first factor was the dose of NPK Mutiara fertiliser (N), consisting of three levels: N1 = 2 g per polybag, N2 = 4 g per polybag, and N3 = 6 g per polybag. The second factor was the concentration of mung bean sprout extract, which consisted of three levels: T0 = 0, T1 = 300 ml/L, and T2 = 600 ml/L. Data were analysed using analysis of variance. If there were significant differences in the treatments, a Duncan test was conducted at the 5% level. The results showed that the application of Mutiara NPK fertiliser at various doses significantly affected plant height, fruit number per plant, and fruit weight per plant, with the best dose being 2 g per polybag. Application of mung bean sprout extract at various concentrations did not significantly affect all observed parameters. The combination of 6 g per polybag of Mutiara NPK fertiliser and 600 ml/L of mung bean sprout extract showed a significantly different interaction on flowering age, and the interaction of 2 g per polybag of Mutiara NPK and 600 ml/L of mung bean sprout extract significantly affected the number of fruits per plant.